2022
DOI: 10.1002/aenm.202202419
|View full text |Cite
|
Sign up to set email alerts
|

Boosting Reversibility and Stability of Zn Anodes via Manipulation of Electrolyte Structure and Interface with Addition of Trace Organic Molecules

Abstract: The practical application of aqueous zinc‐ion batteries (AZIBs) is significantly limited by poor reversibility and stability of the Zn anode. Here, the first time addition of trace organic gamma butyrolactone (GBL) is reported to a typical ZnSO4 electrolyte to controllably manipulate the electrolyte structure and interface. Judiciously combined experimental characterization and theoretical computation confirm that the GBL additive weakens the bonding strength between Zn2+ ion and solvated H2O and rearranges th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(25 citation statements)
references
References 34 publications
0
25
0
Order By: Relevance
“…14,16 One of the optimization strategies is to reduce the H 2 O proportion in solvated Zn(H 2 O) 6 2+ by adding electrolyte additives that have high affinity to Zn 2+ , which can avoid the accumulation of active H 2 O on the EDL structure during the desolvation process. 17–23 However, the enhanced cycling stability comes at the expense of increasing the polarization voltage due to the larger de-solvation penalty. Alternatively, introducing electrolyte additives that have higher adsorption energy on the Zn surface than H 2 O is also capable of altering the EDL structure and thus improving the cycling stability of Zn anodes.…”
Section: Introductionmentioning
confidence: 99%
“…14,16 One of the optimization strategies is to reduce the H 2 O proportion in solvated Zn(H 2 O) 6 2+ by adding electrolyte additives that have high affinity to Zn 2+ , which can avoid the accumulation of active H 2 O on the EDL structure during the desolvation process. 17–23 However, the enhanced cycling stability comes at the expense of increasing the polarization voltage due to the larger de-solvation penalty. Alternatively, introducing electrolyte additives that have higher adsorption energy on the Zn surface than H 2 O is also capable of altering the EDL structure and thus improving the cycling stability of Zn anodes.…”
Section: Introductionmentioning
confidence: 99%
“…Huang et al found that the addition of γ-butyrolactone (GBL) could significantly improve the Zn electroplating/stripping performance. 148 GBL weakened the solvation between Zn 2+ and H 2 O, which rearranged the bonding network between particles and reduced the activity of water, inhibiting the formation of corrosion and byproducts (Fig. 11e).…”
Section: Advances In Foms Used As Protection Layers In Secondary Meta...mentioning
confidence: 99%
“…(e) Schematic illustration of Zn deposition behaviors in ZnSO 4 and ZnSO 4 -GBL electrolytes. Reproduced with permission 148. Copyright 2022, Wiley-VCH GmbH.…”
mentioning
confidence: 99%
“…Furthermore, they could engage in constructing Zn 2 + solvation sheath and confine the free water molecules, which suppresses waterinduced side reactions and widens water splitting voltage. [68] There are various kinds of organic molecule additives have been used, such as, surfactants [69] (e. g., SDS, TBA 2 SO 4 , SDBS), polymers [70] (e. g., PEO, PAM, PSS), chelating agent [71] (e. g., Na 4 EDTA) and organic solvent (e. g., Et 2 O, EG, DMC, DMSO, NMP, DMF). [29,72] Taking the sodium dodecyl sulfate (SDS) surfactant additive as an example.…”
Section: Electrolyte Additivesmentioning
confidence: 99%